Introduction of Corporate Governance Principles in the Higher Pedagogical Education System (Experience of the Republic of Kazakhstan) - Sankhayeva, Aliya; Shkutina, Larissa; Mirza, Nataliya; Zhakisheva, Gulbahram; Ospanova, Madina (Opción, 2019)
The article discusses the prerequisites for the emergence of corporate gov- ernance and the features of the application of the principles of corporate organization of activities in the educational sphere. The approaches to the introduction of corporate governance in the practical experience of univer- sities, focused on the socio-economic performance of educational activities and ensuring the quality of specialist training, have been considered. The research objective is to review the key concepts of a corporate governance model and identify the opportunities and benefits of their implementation in the practice of the higher pedagogical education system in Kazakhstan. The research methodology is based on using a method of an expert survey of administration representatives of pedagogical universities of Kazakh- stan. The practical significance of the study lies in the description of rec- ommendations on the implementation of corporate governance principles in the practice of the higher pedagogical education system in Kazakhstan. Research results demonstrate that the main changes that should occur in the educational management system as a result of the introduction of corporate governance principles lie in the redistribution of the role, competencies, and powers from state bodies to the Supervisory Board and executive bodies in key management issues, as well as changes in corporate culture.